Antagonistic Mechanisms of Bacillus methylotrophicus and Bacillus subtilis: Exploring Cell Wall-Degrading Enzymes and Siderophore Production for Foliar Blight Management in Wheat - Neha Saini; Vindhya Bundela; Ajay Veer Singh (Research Perspectives of Microbiology and Biotechnology Vol. 9, 2025)
Bipolaris sorokiniana and Alternaria triticina are major cereal pathogens causing spot blotch and leaf blight disease in wheat, with yield losses of up to 85%. These play a central role in wheat foliar blight pathogens of wheat so effective management is essential for sustainable production. Bacillus methylotrophicus (P10) and Bacillus subtilis (UP11) are effective biocontrol agents against foliar blight pathogens Alternaria triticina and Bipolaris sorokiniana. Dual culture assays showed significant growth inhibition, with P10 and UP11 reducing pathogen growth by 77.56% and 67.83% for A. triticina and 73.97% and 62.16% for B. sorokiniana. These strains produce cell wall-degrading enzymes (chitinase, protease, \(β\)-1,3-glucanase) and siderophores, peaking at 96 hours in co-cultures with pathogens. Antibiosis and direct inhibition are the primary mechanisms by which these strains suppress the mycelial growth of Bipolaris sorokiniana and Alternaria triticina, emphasizing their role as sustainable biocontrol agents in managing wheat diseases. Their potential as biological control agents underscores the need for further investigation as bioactive ingredients in biopesticide formulations.